Adventure of Jayangrana Pewayangan Sasak Sebagai Ide Perancangan Karakter Tokoh Visual Game Platfrom - Lalu Ade Sukmajayadi; Sunardy Kasim; Muhammad Arfa (Universitas Bumigora, 2021)
The Sasak puppet character as the idea for designing a visual platform game entitled Adventure Of Jayangrana is based on the desire to introduce the Sasak wayang art in the form of games to the younger generation. With this design, it is hoped that the younger generation can get to know the Sasak puppet characters and motivate the younger generation to preserve traditional arts, especially Sasak puppetry as an effort to develop a Sasak culture in contemporary media. The characters in the Sasak puppets are packaged in a contemporary form by adopting them into the form of a platform game visual design entitled Adventure Of Jayangrana. The results of this game's visual concept design are character design, layout design, character animation, and background design. Keyword: Game, Platformer, Sasak puppet